2007
DOI: 10.1111/j.1348-0421.2007.tb03952.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Examination of the Dormant Spore and the Sporulation of Paenibacillus motobuensis Strain MC10

Abstract: Spore-forming bacteria are generally stained Grampositively. However, spore-forming bacteria isolated from air and soil are often stained Gram-negatively. MC10 strain of Paenibacillus motobuensis is a newly isolated strain from soil compost in Okinawa, but is stained Gram-negatively though it produces definite endospores (8). This bacterium has a cell wall structure characteristic of ordinary Gram-positive bacteria according to electron microscopic examination (8). At present the mechanisms of Gram-negative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Sporulation process of Paenibacillus polymyxa strain ShX301 was described [1] , which was similar to that described in P. motobuensis by Iida et al [2] . While other four strains (Hb1, Hb6, ShX302 and ShX303) of P. polymyxa also shared the same characteristics with strain ShX301.…”
Section: Datasupporting
confidence: 72%
“…Sporulation process of Paenibacillus polymyxa strain ShX301 was described [1] , which was similar to that described in P. motobuensis by Iida et al [2] . While other four strains (Hb1, Hb6, ShX302 and ShX303) of P. polymyxa also shared the same characteristics with strain ShX301.…”
Section: Datasupporting
confidence: 72%
“…1b, 16S rRNA gene sequence and phylogenetic evolution analysis showed that LY5201 have a high degree of similarity (92%) with Paenibacillus motobuensis NR 043153.1. It also exhibited the typical biochemical characteristics of P. motobuensis [22] as indicated in Table S1 (supporting data). The strain LY5201 was identi ed as P. motobuensis LY5210.…”
Section: Isolation and Identi Cation Of Ly5201mentioning
confidence: 73%
“…Disinfectant activity against bacterial spores. Most of the contaminating bacteria we identified are known or presumed to form spores, 20,26,49 raising the possibility that the bacteria existed as spores during decontamination. Because spores can be more resistant to disinfection and sterilization than vegetative forms, 44 we sought to compare the killing activity of the different disinfectants against matched pairs of spores and vegetative forms.…”
Section: Resultsmentioning
confidence: 99%
“…Initial attempts to generate spores of the isolated contaminant bacteria under several previously reported induction conditions were unsuccessful. 20,26,49 Instead, we resorted to a well-established spore former, G. stearothermophilus, which is widely used as a biologic indicator for testing autoclave function. 19 Spores and vegetative forms of G. stearothermophilus were exposed briefly (15 min) to various concentrations of each disinfectant in PBS and tested for survivors by growth on agar plates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation